2005
DOI: 10.1128/jcm.43.2.572-576.2005
|View full text |Cite
|
Sign up to set email alerts
|

DNA Macrorestriction Analysis of Nontypeable Group B Streptococcal Isolates: Clonal Evolution of Nontypeable and Type V Isolates

Abstract: Group B streptococci (GBS) are serotyped according to capsular polysaccharide (CPS) type (Ia to VIII); an isolate is classified as nontypeable (NT) if no detectable CPS is found. Surface-localized protein antigens (␣,␤, R1, and R4) serve as additional markers to classify GBS isolates, which is particularly useful since NT isolates often express one or more of these proteins. To compare genetic resemblance among isolates with similar protein profiles, we studied 58 NT isolates digested with the SmaI macrorestri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…Previous studies characterizing GBS isolates have found a relationship between DNA macrorestriction band patterns and serotype/protein profile, especially for type V/R1,R4 and NT/R1,R4 isolates (1). The same study also found remarkable heterogeneity within the NT/R4 group compared with typeable isolates (1). However, the distribution of molecular serotypes and surface protein antigen genes associated with NT isolates is not known.…”
Section: Streptococcus Agalactiae (Group B Streptococcus [Gbs]) Is a mentioning
confidence: 59%
See 3 more Smart Citations
“…Previous studies characterizing GBS isolates have found a relationship between DNA macrorestriction band patterns and serotype/protein profile, especially for type V/R1,R4 and NT/R1,R4 isolates (1). The same study also found remarkable heterogeneity within the NT/R4 group compared with typeable isolates (1). However, the distribution of molecular serotypes and surface protein antigen genes associated with NT isolates is not known.…”
Section: Streptococcus Agalactiae (Group B Streptococcus [Gbs]) Is a mentioning
confidence: 59%
“…Previous studies have shown that certain surface antigenic proteins are frequently associated with a given serotype, and such associations are utilized in classifying GBS isolates (1,16,23). Associations between molecular serotypes and protein antigens may represent specific evolutionary lineages and could lack functional significance, but an interesting hypothesis predicts that immune selection has favored strains with specific combinations of protein antigens because it improves their fitness (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their capsular polysaccharides, GBS isolates can be classified into nine different serotypes (Ia, Ib, and II to VIII), with serotypes Ia, II, III, and V being the predominant causes of human GBS diseases (11,29). In particular, the serotypes most commonly causing neonatal infections are Ia, III, and V (32), with the latter being the main serotype recovered from patients of all age groups, including nonpregnant adults (1,19).Some of the best-characterized GBS protein antigens belong to the alpha-like protein (Alp) family, a class of surface proteins characterized by internal long identical tandem repeats. These proteins are named alpha, Alp1, Alp2, Alp3, Alp4, and Rib (28).…”
mentioning
confidence: 99%